Beyond arithmetic skills: integrating interactive learning, gradual practice, and reward systems to foster children’s numeracy development - Nadia Rahmadani; Difa’ul Fikri Jayyid; Abubakar Siddiq Uba (Eduvista: Journal of Education and Innovation, 2026)
Mathematics learning continues to face challenges related to low student engagement, motivation, and conceptual understanding of basic arithmetic operations. This study aims to analyze the implementation of an integrated numeracy learning approach combining interactive learning, gradual practice activities, and a reward system to improve children’s numeracy skills and learning motivation. This study employed a descriptive qualitative approach supported by simple quantitative data obtained through participant observation, initial and final assessments, and documentation involving 18 children aged 5–12 years in Peganjaran Village. The findings revealed that the implemented learning approach contributed to improvements in learning engagement, self-confidence, numeracy skills, and learning persistence. These improvements were reflected in children’s increased willingness to participate, shifts in problem-solving strategies from procedural approaches toward conceptual understanding, and the development of learning motivation through an effort-oriented reward system. These findings indicate that integrating interactive learning, gradual practice, and a proportional reward system can establish a more active, enjoyable, and developmentally appropriate numeracy learning environment. Abstrak Pembelajaran matematika masih sering menghadapi tantangan berupa rendahnya keterlibatan, motivasi, dan pemahaman konseptual peserta didik terhadap operasi hitung dasar. Penelitian ini bertujuan untuk menganalisis implementasi pembelajaran numerasi berbasis pembelajaran interaktif, latihan bertahap, dan reward system dalam meningkatkan kemampuan numerasi serta motivasi belajar anak. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan dukungan data kuantitatif sederhana yang diperoleh melalui observasi partisipatif, asesmen awal dan akhir, serta dokumentasi terhadap 18 anak usia 5–12 tahun di Desa Peganjaran. Hasil penelitian menunjukkan bahwa pendekatan pembelajaran yang diterapkan mampu meningkatkan keterlibatan belajar, kepercayaan diri, kemampuan numerasi, dan ketekunan anak. Peningkatan tersebut terlihat dari keberanian anak dalam berpartisipasi, perubahan strategi penyelesaian masalah dari prosedural menuju pemahaman konseptual, serta berkembangnya motivasi belajar melalui reward system yang berorientasi pada usaha dan perkembangan individu. Temuan ini menunjukkan bahwa integrasi pembelajaran interaktif, latihan bertahap, dan reward system mampu menciptakan lingkungan belajar numerasi yang lebih aktif, menyenangkan, dan sesuai dengan kebutuhan perkembangan anak.